Students’ Understanding of the Independent Curriculum at Serambi Mekkah University’s Faculty of Teacher Training - sufi, ibrahim; Akmal, Nurul; Zubainur, Cut Morina; Almukarramah, A; Firmansyah, Juli (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
Various problems experienced by teachers and prospective teacher students in following and implementing the currently applicable Independent Learning and Independent Curriculum. The level of understanding for teachers and students about the implementation the Independent Curriculum has various interpretations and interpretations. The purpose of this study was to determine the level of understanding of students of the teaching the implementation design of the Independent Curriculum in the field. The time of the research was conducted at the teaching faculty of Serambi Mekkah with final year students as our data source. The data analysis method used was descriptive qualitative in the form of results from observations and questionnaire data answered by the respondents. The data from the analysis showed that (a) the number of students who really understood the Independent Curriculum was 85.14%; (b) respondents received information about the Independent Curriculum which mostly came from university pages and news media; (c) The activities that were most in demand by respondents were Internships or Field Work; and (d) there were 69.80% of them who were very happy with the Curriculum because it helped respondents improve personal skills which became capital in carrying out the teaching and learning process in the future.